The 2008 Amendments to the Federal Higher Education Act: Are We on the Right Track? - Zulick, Bradford J.; Stampen, Jacob O. (My University, 2009)
This policy brief summarizes the Higher Education Amendments of 2008 (HEA 2008) and the evolution of the Higher Education Act since 1965, particularly the evolution of federal and non-federal forms of financial assistance aimed at increasing educational opportunity and attainment in the United States. Because the act's extensive academic support programs, such as TRIO and GEAR UP, require separate attention, this analysis of HEA 2008 is limited to a general overview of the student financial aid aspects of what appears to be its overarching theme: to promote more effective and efficient collaboration among the federal government, state governments, colleges and universities, lending agencies, and the private sector in order to improve college education and make it more affordable. The authors then address questions about the evolution of the Higher Education Act and whether HEA 2008 is likely to increase the ability of the American higher education system to achieve its historic goals. The brief concludes with findings and suggestions for future improvement.
Keywords: Federal Higher Education Act; Accountability, Autonomy, and Politics